Ketepatan Pemberian Solidaritas COVID-19 terhadap Lansia - Panjaitan, Hilda Carmitha; Burdam, Frisca Joice; Nanlohy, Maria Fransina Penina (Jurnal Cakrawala Promkes, 2021)
During the COVID-19 pandemic, there was an increase in solidarity in the community. However, COVID-19 solidarity, which is not only given to vulnerable groups, can cause only a few elderly to receive assistance. This study aimed to analyze the accuracy of the targeting of COVID-19 solidarity assistance aimed at the elderly as the most vulnerable group, concerning things that can be understood about the elderly in the midst of the COVID-19 pandemic. This research is a descriptive study with a semi-quantitative approach. This research was conducted by tracing and analyzing news about Covid-19 Solidarity, which was published in online media. The research period was started from March to June 2020. Data collection techniques were carried out through documentation, observation, and literature studies. The study found that out of 352 news, only 16 news contained the target to the elderly. So it can be concluded that during the COVID-19 pandemic, only a few elderly received assistance. This is due to the negative stigma regarding the elderly. Suggestions for future researchers, to be able to research by gathering news in a larger number to get wider news information from each region.Keywords: COVID-19,  Elderly,  Social solidarity,  Social stigma